1997
DOI: 10.1097/00001756-199712010-00021
|View full text |Cite
|
Sign up to set email alerts
|

Photic control of nitric oxide synthase activity in golden hamster retina

Abstract: A characterization of nitric oxide synthase (NOS) in the golden hamster retina was performed. Enzymatic activity was partially Ca2+ and calmodulin-dependent, required NADPH, and was inhibited by L-arginine analogs. Retinal NOS activity was higher at midnight than at midday. When the hamster were placed under constant darkness for 24 or 48 h, and killed at equivalent time points, representing subjective day and subjective night respectively, the differences in NOS activity disappeared. One hour of darkness duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…In a previous report, we showed that NOS activity is regulated by the photic information (Llomovatte et al . 1997) in a similar way to that showed herein for l ‐arginine uptake.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In a previous report, we showed that NOS activity is regulated by the photic information (Llomovatte et al . 1997) in a similar way to that showed herein for l ‐arginine uptake.…”
Section: Discussionmentioning
confidence: 83%
“…A necessary (although not suf®cient) condition to prove this idea would be to demonstrate changes in NOS activity in response to photic stimulus. Indeed, in a previous report, we demonstrated that retinal NOS activity in the hamster is regulated by light signals (Llomovatte et al 1997), being higher during the night than during the day. In addition, we showed that cGMP levels in the hamster retina are signi®cantly higher during the dark than during the light phase (Faillace et al 1995), in a similar manner than NOS activity.…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…), and in the mammalian retina, NOS activity oscillates over the course of a day (Llomovatte et al . ; Zhang et al . ), we thereby investigated whether NO elicited a circadian phase‐dependent modulation of L‐VGCCs in avian cone photoreceptors.…”
mentioning
confidence: 99%